Presence of fibroids in the absence of uterus- Mayer-Rokitansky-Küster-Hauser syndrome with fibroids: a case report - B. Ramesh,; Shivalingappa, Nayana M.; Konda, Kiran R.; Suryanarayana, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is rare congenital anomaly with complete absence of uterus and upper part of vagina. Fibroids are one of the most common benign tumours arising in women. Fibroids arising from Mullerian remnants are very rare. These fibroids often pose difficulty in diagnosis and management. Here, we report a rare case of fibroids arising from Mullerian remnants in MRKH syndrome and the treatment provided for the patient.